Maqashid Sharia Analysis of Community Perceptions in Determining Zakat Fitrah Recipients - Tambunan, Jannus; Muhardinata, Imam (STAI Serdang Lubuk Pakam, 2023)
In order for the distribution of zakat to be done correctly and fairly, it should be paid through an official amil zakat appointed by the government or from the community (private institutions). This research aims at two things, namely: (a) the perception and practice of the community in determining zakat recipients and (b) maqashid sharia analysis of community perceptions in determining zakat recipients. This research uses descriptive-analytical approach by describing, describing the practice of paying zakat fitrah to orphans, Quranic teachers and widows analyzed from Maqashid Sharia. Research data: First, field data through observation, interviews, documentation studies. Second, literature data by reviewing various literatures to collect and analyze data. In general, the community pays their zakat to Quranic teachers, orphans, and widows because of the factor of not being trustworthy in the amil zakat management, displeasure with the amil zakat management and orphans, Quranic teachers and widows have a burden of family needs and their economic conditions are difficult. This is in accordance with Maqashid Sharia at the level of hajiyyah (needs that must be met) because some are included in the category of the poor who are entitled to receive zakat.